(untitled) - Nassar, David S. (Hoboken, N.J., 2006)
David Nassar delivers a complete and proven system for aggressively and successfully trading in today's markets in Ordinary People, Extraordinary Profits. He explains the fundamentals of technical analysis and risk management, giving you a solid foundation to approach the market, and then describes a variety of trading strategies that will help you make consistently large profits without undue risk. Unlike other trading advisors who advocate a single approach to trading, Nassar provides a variety of strategies you can choose. In addition, he explains how to use new trading instruments such as E-Mini contracts, options, and exchange-traded funds. If you're looking for a complete, proven system for aggressively trading the stock market, this book is an ideal guide.
Keywords: Investment analysis,Portfolio management,Risk management,Investments,Phân tích đầu tư,Quản lý danh mục đầu tư,Quản lý rủi ro,Các khoản đầu tư